2015
DOI: 10.1186/s12885-015-1040-4
|View full text |Cite
|
Sign up to set email alerts
|

Screening of exon 11 of BRCA1 gene using the high resolution melting approach for diagnosis in Moroccan breast cancer patients

Abstract: BackgroundIdentification of specific mutations in cancer patients may lead to the discovery of genes, which can affect susceptibility and/or prognosis. It has previously been reported that mutations in BRCA1 and BRCA2 genes are linked to breast cancer. Here, we evaluated the use of the High Resolution Melting (HRM) approach to screen for mutations in exon 11 of BRCA1 gene in Moroccan patients.MethodsHRM analysis was used to screen exon 11 from 71 breast cancer patients in order to detect different variants. Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…analysis has been demonstrated to be useful for the diagnosis of lung adenocarcinoma (45) and Moroccan breast cancer (46); Studies using HRM analysis showed heterozygous mutations in COL1A1 and COL1A2 genes are associated with osteogenesis imperfecta (47).…”
Section: Discussionmentioning
confidence: 99%
“…analysis has been demonstrated to be useful for the diagnosis of lung adenocarcinoma (45) and Moroccan breast cancer (46); Studies using HRM analysis showed heterozygous mutations in COL1A1 and COL1A2 genes are associated with osteogenesis imperfecta (47).…”
Section: Discussionmentioning
confidence: 99%
“…BRCA1 is characterized by a zinc-binding RING finger domain at the amino terminus and BRCA1 carboxyl terminal (BRCT) domain at the carboxyl terminus (Zheng et al, 2000). Among the 22 exons, exon11 having 3426bp, is a large central exon of BRCA1 gene and represents about 60% of the coding sequences (Khachibi et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Studies using HRM analysis showed that methylation of the BRCA1 promoter in peripheral blood DNA is associated with triple-negative and medullary breast cancer 11 . It has been reported that screening BRCA1 gene using HRM analysis was used for diagnosis of moroccan breast cancer 12 and lung adenocarcinoma 13 .…”
Section: Resultsmentioning
confidence: 99%